Electromagnetic Wave Theory and Applications - Kong, Jin Au; Ali, Sami M.; Shin, Robert T.; Yang, Ying-Ching Eric; Habashy, Tarek M.; Poh, Soon Y.; Atkins, Robert G.; Chang, Ike; Gu, Qizheng; Lee, Check-Fu; Li, Kevin; Sheen, David M.; et al. (Research Laboratory of Electronics (RLE) at the Massachusetts Institute of Technology (MIT), 1989)
Contains table of contents for Section 3 and reports on seven research projects. Joint Services Electronics Program Contract DAAL03-89-C-0001 National Science Foundation Contract ECS 86-20029 Schlumberger- Doll Research U.S. Army Research Office Contract DAAL03 88-K-0057 National Aeronautics and Space Administration Contract NAGW-1617 U.S. Navy - Office of Naval Research Contract N00014-89-J-1107 National Aeronautics and Space Administration Contract NAGW-1272 National Aeronautics and Space Administration Contract 958461 Simulation Technologies Contract DAAH01-87-C-0679 U.S. Army Corp of Engineers Contract DACA39-87-K-0022 WaveTracer, Inc. U.S. Navy - Office of Naval Research Contract N00014-89-J-1019 U.S. Air Force Systems - Electronic Systems Division Contract F19628-88-K-0013 Digital Equipment Corporation International Business Machines Corporation U.S. Department of Transportation Contract DTRS-57-88-C-00078